3D Printing - Cvetković, Dragan (IntechOpen, 2018)
This book, "3D Printing", is divided into two parts: the first part is devoted to the relationship between 3D printing and engineering, and the second part shows the impact of 3D printing on the medical sector in general. There are five sections in the first part (sections are dedicated to stereolithography, new techniques of high-resolution 3D printing, application of 3D printers in architecture and civil engineering, the additive production with the metal components and the management of production by using previously mentioned technology in more complex ways). There are four chapters in the second part with the following topics: education of medical staff through surgical simulations, tissue engineering and potential applications of 3D printing in ophthalmology and orthopedics.